CYP2D6 Genetic Variation and Its Implication for Vivax Malaria Treatment in Madagascar - Mehlotra, Rajeev K.; Gaedigk, Andrea; Howes, Rosalind E.; Rakotomanga, Tovonahary A.; Ratsimbasoa, Arsene C.; Zimmerman, Peter A. (Frontiers in Pharmacology, 2021)
Plasmodium vivax is one of the five human malaria parasite species, which has a wide geographical distribution and can cause severe disease and fatal outcomes. It has the ability to relapse from dormant liver stages (hypnozoites), weeks to months after clearance of the acute blood-stage infection. An 8-aminoquinoline drug primaquine (PQ) can clear the hypnozoites, and thus is commonly used as an anti-relapse therapeutic agent. Recently, a number of studies have found that its efficacy is compromised by polymorphisms in the cytochrome P-450 2D6 (CYP2D6) gene; decreased or absence of CYP2D6 activity contributes to PQ therapeutic failure. The present study sought to characterize CYP2D6 genetic variation in Madagascar, where populations originated from admixture between Asian and African populations, vivax malaria is endemic, and PQ can be deployed soon to achieve national malaria elimination. In a total of 211 samples collected from two health districts, CYP2D6 decreased function alleles CYP2D6*10, *17, *29, *36+*10, and *41 were observed at frequencies 3.55–17.06%. In addition, nonfunctional alleles were observed, the most common of which were CYP2D6*4 (2.13%), *5 (1.66%), and the *4x2 gene duplication (1.42%). Given these frequencies, 34.6% of the individuals were predicted to be intermediate metabolizers (IM) with an enzyme activity score (AS) ≤ 1.0; both the IM phenotype and AS ≤ 1.0 have been found to be associated with PQ therapeutic failure. Furthermore, the allele and genotype frequency distributions add to the archaeological and genomic evidence of Malagasy populations constituting a unique, Asian-African admixed origin. The results from this exploratory study provides fresh insights about genomic characteristics that could affect the metabolism of PQ into its active state, and may enable optimization of PQ treatment across human genetic diversity, which is critical for achieving P. vivax elimination.